2017
DOI: 10.15666/aeer/1503_771783
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chemical and Non-Chemical Weed Management Methods on Chemical and Biological Properties of Soil in Potato Cultivation in Ardabil Province, Iran

Abstract: Abstract. The present study explores the effect of weed management practices on the properties of soil, including microbial biomass carbon (MBC), soil organic carbon (SOC), basal respiration (BR), induced respiration (IR), and microbial quotient (MQ) in potato cultivation at two agricultural research stations of Alarogh and Samian in Ardabil Province, Iran. We carried out a randomized complete block design with three replications. The treatments were as follows: 1) Trifluralin herbicide (TR), 2) Metribuzin her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…It might be due to light passes through white plastic mulch and its stimulate the germination of weeds but because of the low temperature during the crop growth period it could not prevent weeds germination and the result, may be stimulated weed species and causes of weed germination. This was reported by Azadbakht et al (2017) and Majd et al (2014).…”
Section: Effect On Weedssupporting
confidence: 74%
“…It might be due to light passes through white plastic mulch and its stimulate the germination of weeds but because of the low temperature during the crop growth period it could not prevent weeds germination and the result, may be stimulated weed species and causes of weed germination. This was reported by Azadbakht et al (2017) and Majd et al (2014).…”
Section: Effect On Weedssupporting
confidence: 74%
“…However, the least amount of weed biomass was observed in treatments of wheat and canola mulches and it was found that these treatments can reduce weed biomass compared to weed infested treatment by a rate of 83% and 81% decrease, and this reflects the ability of plant residues in suppressing weeds and preventing their growth as well as preventing the spread of weeds and reducing the crop yield (Duppong et al, 2004). Plant residues are not only affect the soil but also can affect the germination, survival, growth and competitive ability of weed and crop plants (Majd et al, 2014;Pawlonka et al, 2015;Azadbakht et al, 2017). Although in current study, the lowest biomass of broadleaf and grass weeds showed a significant difference with the weed infested treatment and broadleaf weeds had more biomass than grass weeds (Fig.…”
Section: Weed Biomassmentioning
confidence: 57%